Problem-Based Learning and Students Critical Thinking in Fiqh Learning: Problem-Based Learning dalam Berpikir Kritis dan Prestasi Belajar Fikih - Muhammad Khadafi; ahmadi suradi; mindani mindani (Universitas Muhammadiyah Sidoarjo, 2026)
Background: Islamic Religious Education plays an important role in shaping students’ intellectual and spiritual development; however, classroom practice in Fiqh learning often relies on conventional teacher-centered methods that limit students’ engagement and conceptual understanding. Specific Background: In many madrasah contexts, including MTs 01 Darussalam Kepahiang, students show limited participation and learning outcomes below the expected standard, particularly when learning abstract Islamic legal concepts that require deeper reasoning. Knowledge Gap: Although Problem-Based Learning (PBL) has been widely studied in general subjects, its application in Fiqh learning within Islamic religious education remains relatively limited. Aims: This study investigates the relationship between the implementation of Problem-Based Learning and students’ critical thinking skills and learning achievement in the Fiqh subject. Results: Using a quantitative quasi-experimental design with a Nonequivalent Control Group Design involving two classes, the experimental group applying PBL demonstrated higher improvement in post-test scores (81.7) compared with the control group using conventional instruction (70.4), with a statistical significance value of 0.001 (<0.05). Novelty: The study contextualizes Problem-Based Learning within Islamic Religious Education by integrating critical thinking development and Fiqh learning outcomes in a madrasah environment. Implications: These findings indicate that Problem-Based Learning supports active student participation, deeper conceptual understanding of Islamic law, and improved academic performance, suggesting its relevance as a student-centered instructional approach for Fiqh learning in Islamic educational institutions. Highlights • Experimental class displayed higher post-test score growth than the comparison class• Classroom observation recorded stronger discussion participation and questioning behavior• Quasi-experimental analysis identified statistically significant group differences (p < 0.05) Keywords Problem-Based Learning; Critical Thinking; Fiqh Learning Achievement; Islamic Religious Education; Quasi Experimental Design